Pulmonary arteriovascular malformation: a rare cause of unexplained hypoxia and acute dyspnoea in young patients. (19th December 2014) - Iqbal, Nousheen; Rehman, Karim Abdur; Khan, Javaid Ahmed; Haq, Tanveer Ul
Abstract : Pulmonary arteriovenous malformations (PAVMs) are anomalous vascular connections between arteries and veins in the lung and comprise of two types, simple and complex. PAVMs are associated with congenital conditions such as hereditary haemorrhagic telengiectasia along with acquired causes. We present a case of a 26-year-old man who presented with dyspnoea, palpitations and decreased oxygen saturation as an initial presentation of PAVM, which was treated successively with embolisation.